THE EFFECT OF INTELLECTUAL CAPITAL, OPERATING CAPACITY AND INTANGIBLE ASSET ON FIRM PERFORMANCE MODERATION BY AGENCY COST - Sitorus, Riris Rotua; Fransiska , Fenny (Universitas Tidar, 2022)
The purpose of this study is to analyze the effect of intellectual capital, operating capacity, intangible assets on company performance moderated by agency costs. This study utilizes information taken from financial reports that are listed on the Indonesia Stock Exchange (IDX) using purposive sampling that meets the exploratory steps. The research period was taken for 5 years from 2017 to 2021 with the amount of information used, namely 50 samples of manufacturing companies in the consumer goods sector. The research method uses STATA with secondary data types. The results of the study state that intellectual capital and operating capacity partially affect the company's performance, while intangible assets partially do not affect the company's performance. The results of the moderating variable state that agency costs can moderate the intellectual capital of intangible assets on company performance and agency costs cannot moderate operating capacity on company performance.